A model-based optimization study on greywater reuse as an alternative urban water resource - Khor, C.S. (Elsevier B.V., 2020)
Integrated urban water management (IUWM) aims to promote water supply not only from conventional sources but also from wastewater reuse in part to address issues such as water scarcity. In line with the situation, this work concerns greywater reuse in synthesizing and retrofitting water network at household and community levels. We consider various water-using activities and suitable wastewater treatment technologies through a nonlinear optimization model based on a superstructure which incorporates multiple alternatives for greywater reuse, regeneration (treatment), and recycle. The model objective aims to minimize freshwater consumption and/or wastewater generation in addition to the fixed capital cost of installing the pipes and the variable operating cost of water pumping. The optimization procedure is carried out subject to complying with constraints to reduce the contamination level to acceptable reuse limits or otherwise for disposal or discharge to the environment while meeting various real-world design and operating specifications that include requirements for minimum water service and hygienic reasons. A real-world case study is illustrated on a residential household with four occupants by combining engineering experience and physical insights to obtain a realistic model representation of the problem. To circumvent the solution challenge presented by the nonconvex formulation, we apply a convexification strategy to handle the concave terms in the objective function. The proposed approach has demonstrated that significant reductions in freshwater use are possible. Â© 2020